Association with HLA-DRβ1 position 37 distinguishes juvenile dermatomyositis from adult-onset myositis. Issue 14 (31st January 2022) - Deakin, Claire T; Bowes, John; Rider, Lisa G; Miller, Frederick W; Pachman, Lauren M; Sanner, Helga; Rouster-Stevens, Kelly; Mamyrova, Gulnara; Curiel, Rodolfo; Feldman, Brian M; Huber, Adam M; Reed, Ann M; et al.
Abstract: Juvenile dermatomyositis (JDM) is a rare, severe autoimmune disease and the most common idiopathic inflammatory myopathy of children. JDM and adult-onset dermatomyositis (DM) have similar clinical, biological and serological features, although these features differ in prevalence between childhood-onset and adult-onset disease, suggesting that age of disease onset may influence pathogenesis. Therefore, a JDM-focused genetic analysis was performed using the largest collection of JDM samples to date. Caucasian JDM samples ( n = 952) obtained via international collaboration were genotyped using the Illumina HumanCoreExome chip. Additional non-assayed human leukocyte antigen (HLA) loci and genome-wide single-nucleotide polymorphisms (SNPs) were imputed. HLA-DRB1 * 03:01 was confirmed as the classical HLA allele most strongly associated with JDM [odds ratio (OR) 1.66; 95% confidence interval (CI) 1.46, 1.89; P = 1.4 × 10 −14 ], with an independent association at HLA-C * 02:02 (OR = 1.74; 95% CI 1.42, 2.13, P = 7.13 × 10 −8 ). Analyses of amino acid positions within HLA-DRB1 indicated that the strongest association was at position 37 (omnibus P = 3.3 × 10 −19 ), with suggestive evidence this association was independent of position 74 (omnibus P = 5.1 × 10 −5 ), the position most strongly associated with adult-onset DM. Conditional analyses also suggested that the association at position 37 of HLA-DRB1 was independent of some alleles of the Caucasian HLA 8.1 ancestral haplotype (AH8.1) such as HLA-DQB1 * 02:01 (OR = 1.62; 95% CI 1.36, 1.93; P = 8.70 × 10 −8 ), but not HLA-DRB1 * 03:01 (OR = 1.49; 95% CR 1.24, 1.80; P = 2.24 × 10 −5 ). No associations outside the HLA region were identified. Our findings confirm previous associations with AH8.1 and HLA-DRB1 * 03:01, HLA-C * 02:02 and identify a novel association with amino acid position 37 within HLA-DRB1, which may distinguish JDM from adult DM.